Cardiac Recovery: Webcast September 24 2024 - Miguel A. Quiñones; James B. Young; Arvind Bhimaraj; Jane E. Wilcox; Manreet K. Kanwar; Stavros G. Drakos (Methodist DeBakey Cardiovascular Journal)
This 61-minute webcast features a conversation about “Cardiac Recovery”—the focus of Issue 20.4. Led by the issue’s editors, the discussion engages the authors on emerging themes and lessons learned while researching and writing the articles. View the video at https://vimeo.com/event/4490511.